End of life in prison: challenges for prisons, staff and prisoners - Richter, Marina (The Routledge Companion to Rehabilitative Work in Criminal Justice, 2019)
The main goal of most systems of criminal justice and most corresponding institutions, such as prisons or forensic psychiatric hospitals, is to eventually release inmates and therefore organize rehabilitative work on the basis that, after their release, they should be able to live a life without further offending. On the contrary, for offenders whose future is constrained to custody and who therefore will most probably die in prison, reinsertion or rehabilitation is not an inherent goal of custody. The chapter will explore the easons (ageing and health conditions, delinquency at a later age and, in particular, a restrictive system of sanctions and security measures) that lead to the increase of end of life cases in prisons. Insights into the situation in selected countries provide some statistical ground for a better understanding of the importance of the phenomenon as well as of differences in cross-national perspective. Different approaches in handling end of life in prisons and related etcal questions are discussed. These approaches deal with challenges on the level of the penentiary system, on the organizational level of the single prison, for the day-to-day work of staff, and for fellow prisoners as well as for the dying prisoners themselves.